2020
DOI: 10.3389/fcell.2020.00618
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Routes Analysis of SARS-CoV-2: A Systematic Review and Case Report

Abstract: The global outbreak of SARS-CoV-2 spread rapidly throughout the world which transmitted among humans through various routes. Asymptomatic (carriers) and possible fecal-oral transmission, resulted into a large-scale spread. These issues pose great challenges to disease diagnosis and epidemic control. We obtained data on 29 cases of COVID-19 patients in Jinan, China, and reported the clinical data of asymptomatic patients confirmed with stool samples positive. Some patients with gastrointestinal infections are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 37 publications
1
87
0
1
Order By: Relevance
“…The rapid outbreak of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that is spread via airborne, droplet, contact, and fecal–oral transmission modes constitutes a worldwide and disruptive challenge to societies [ 1 , 2 ]. Both symptomatic and asymptomatic carriers have been recognized to transmit the SARS-CoV-2 virus via various modes of transmission [ 3 , 4 , 5 ], causing severe respiratory infections among patients receiving medical care in hospitals [ 6 , 7 , 8 , 9 , 10 , 11 ]. Hence, the COVID-19 outbreak has been declared a global public health emergency of international concern by the World Health Organization (WHO) [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid outbreak of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that is spread via airborne, droplet, contact, and fecal–oral transmission modes constitutes a worldwide and disruptive challenge to societies [ 1 , 2 ]. Both symptomatic and asymptomatic carriers have been recognized to transmit the SARS-CoV-2 virus via various modes of transmission [ 3 , 4 , 5 ], causing severe respiratory infections among patients receiving medical care in hospitals [ 6 , 7 , 8 , 9 , 10 , 11 ]. Hence, the COVID-19 outbreak has been declared a global public health emergency of international concern by the World Health Organization (WHO) [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistology studies have revealed the expression levels of ACE2 receptors in the small intestine [ 53 ]. With such an extensive distribution of ACE2 receptors, COVID-19 cases have bridged the connection of disease with the disruption of the digestive system expressed in terms of diarrhea, nausea and vomiting, and abdominal pain [ 54 ]. This could be a reason for the presence of SARS-CoV-2 in the fecal samples until 5 weeks after the patients testing negative for the upper respiratory swab samples [ 54 , 55 ].…”
Section: Evidence For Entry Of Sars-cov-2 Into the Cnsmentioning
confidence: 99%
“…With such an extensive distribution of ACE2 receptors, COVID-19 cases have bridged the connection of disease with the disruption of the digestive system expressed in terms of diarrhea, nausea and vomiting, and abdominal pain [ 54 ]. This could be a reason for the presence of SARS-CoV-2 in the fecal samples until 5 weeks after the patients testing negative for the upper respiratory swab samples [ 54 , 55 ]. GI tract is connected to the central nervous system through the enteric neuronal network regulated by the vagus nerve and sympathetic nerve.…”
Section: Evidence For Entry Of Sars-cov-2 Into the Cnsmentioning
confidence: 99%
“…There was also no development of COVID-19 disease in blood recipients who received blood or its component from a donor with confirmed infection with SARS- CoV- 2 in the post-donation period [ 8 , 9 ]. Nevertheless, the theoretical risk of TTI and TTD associated with SARS-CoV-2 virus does exist and should not be underestimated [ [10] , [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%